The human auditory system : fundamental organization and clinical disorders - Celesia, Gastone G.; Hickok, Gregory (Elsevier B.V., 2015)
"The Human Auditory System: Fundamental Organization and Clinical Disorders provides a comprehensive and focused reference on the neuroscience of hearing and the associated neurological diagnosis and treatment of auditory disorders. This reference looks at this dynamic area of basic research, a multidisciplinary endeavor with contributions from neuroscience, clinical neurology, cognitive neuroscience, cognitive science communications disorders, and psychology, and its dramatic clinical application"--Publisher's description
Keywords: Auditory Cortex -- physiology; Auditory Pathways -- physiology; Auditory perception; Hearing Disorders -- physiopathology; Hearing -- physiology